Sex estimation from fingerprint ridge density. A review of literature - Sharma, Siddharatha; Shrestha, Rijen; Krishan, Kewal; Kanchan, Tanuj (Acta Biomedica Atenei Parmensis, 2021)
Identification has always been very vital in forensic casework. Fingerprint patterns are population-specific and individualistic, that makes fingerprinting an important biological trait in human biology and forensics. Fingerprint is an impression of the friction ridges of the finger-ball, where friction ridges are raised portions of the epidermis. Skin on human fingertips contains ridges and valleys which together forms distinctive patterns. These patterns are fully developed in intra-uterine life and remain unaltered until the death of the individual. Injuries such as cuts, burns and bruises can temporarily damage quality of fingerprints but when fully healed, the patterns are restored. The number of ridges present in a unit area on a fingerprint is called the Fingerprint Ridge Density (FPRD). The epidermal ridge density can be determined by examining two parameters - ridge width and distance between the ridges. The thickness of the epidermal ridges varies between individuals and between the sexes. The present review of literature focuses on the sexual dimorphism on the basis of the FPRD and its possible use in forensic examinations. Most of the studies pertaining to the estimation of sex from the FPRD have been conducted in the last two decades when Mark A. Acree in 1999, devised a method of estimation of sex on Caucasian and African-American descent. The present analysis evaluates the studies found in the PubMed database conducted after Acree, 1999. The estimation of sex from the FPRD is based upon the fact that the females have a fine detailing of ridges and consequently more ridges are covered in a unit space in the fingerprints of females as compared to males. The paper also highlights recent advancements and future perspectives in the area of FPRD. (www.actabiomedica.it)